Foxd4 is essential for establishing neural cell fate and for neuronal differentiation. Issue 6 (3rd April 2017) - Sherman, Jonathan H.; Karpinski, Beverly A.; Fralish, Matthew S.; Cappuzzo, Justin M.; Dhindsa, Devinder S.; Thal, Arielle G.; Moody, Sally A.; LaMantia, Anthony S.; Maynard, Thomas M.
Abstract: Many molecular factors required for later stages of neuronal differentiation have been identified; however, much less is known about the early events that regulate the initial establishment of the neuroectoderm. We have used an in vitro embryonic stem cell (ESC) differentiation model to investigate early events of neuronal differentiation and to define the role of mouse Foxd4, an ortholog of a forkhead‐family transcription factor central to Xenopus neural plate/neuroectodermal precursor development. We found that Foxd4 is a necessary regulator of the transition from pluripotent ESC to neuroectodermal stem cell, and its expression is necessary for neuronal differentiation. Mouse Foxd4 expression is not only limited to the neural plate but it is also expressed and apparently functions to regulate neurogenesis in the olfactory placode. These in vitro results suggest that mouse Foxd4 has a similar function to its Xenopus ortholog; this was confirmed by successfully substituting murine Foxd4 for its amphibian counterpart in overexpression experiments. Thus, Foxd4 appears to regulate the initial steps in establishing neuroectodermal precursors during initial development of the nervous system.